Rancang Bangun Piranti Lunak Pengolah Data Pasca Pengujian Terowongan Angin Kecepatan Rendah Indonesia - Ivransa Zuhdi Pane (Ultimatics : Jurnal Teknik Informatika, 2015)
Data post-processing plays important roles in a wind tunnel test, especially in supporting the validation of the test results and further data analysis related to the design activities of the test objects. One effective solution to carry out the data post-processing in an automated productive manner, and thus eliminate the cumbersome conventional manual way, is building a software which is able to execute calculations and have abilities in presenting and analyzing the data in accordance with the post-processing requirement. Through several prototype development cycles, this work attempts to engineer and realize such software to enhance the overall wind tunnel test activities. Index Terms—software engineering, wind tunnel test, data post-processing, prototype, pseudocode